The impact of the creative performance of agricultural heritage systems on tourists’ cultural identity: A dual perspective of knowledge transfer and novelty perception - Song, Huiqi; Chen, Pengwei; Zhang, Shuning; Chen, Youcheng; Zhao, Weiwei (Frontiers in Psychology, 2022)
Tourism in the Globally Important Agricultural Heritage System (GIAHS) is critical to the inheritance and innovation of excellent traditional farming cultures. Based on social identity theory, this paper explored the process by which agricultural heritage systems’ creative performance influences tourists’ cultural identity through 406 questionnaires from Chinese tourists. The results indicate that creative performance affects tourists’ cultural identity through a dual perspective of knowledge transfer and novelty perception. Furthermore, perceived authenticity acts as a moderator, weakening the impact of creative performance on tourists’ knowledge transfer, while perceived authenticity does not affect the process of tourists’ novelty perception. This research provides a fresh perspective on the sustainable development of agricultural heritage tourism. Meanwhile, it offers theoretical foundations and practical inspirations for the development of agricultural heritage’s creative tourism.